La linguistique peut-elle sortir de son état pré-galiléen ? - Desclés, Jean-Pierre (Neophilologica, 2021)
The future of linguistics implies a better definition of concepts, especially in the semantic analysis. The notion of operator plays an important role in several areas of linguistics, for instance categorical grammars and representations of the meanings of grammatical categories. The general topology makes it possible to mathematize the grammatical concepts (time, aspects, modalities, enunciative operations) by means of operators. Curry’s Combinatorial Logic is an adequate formalism for composing and transforming operators at different levels of analysis that connect the semiotic expressions of languages (the observables) with their semantico-cognitive interpretations. The article refers to many studies that develop the points discussed.